Bioinks for bioprinting functional meniscus and articular cartilage. Issue 4 (October 2017) - Critchley, Susan E; Kelly, Daniel J
3D bioprinting can potentially enable the engineering of biological constructs mimicking the complex geometry, composition, architecture and mechanical properties of different tissues and organs. Integral to the successful bioprinting of functional articular cartilage and meniscus is the identification of suitable bioinks and cell sources to support chondrogenesis or fibrochondrogenesis, respectively. Such bioinks must also possess the appropriate rheological properties to be printable and support the generation of complex geometries. This review will outline the parameters required to develop bioinks for such applications and the current recent advances in 3D bioprinting of functional meniscus and articular cartilage. The paper will conclude by discussing key scientific and technical hurdles in this field and by defining future research directions for cartilage and meniscus bioprinting.